2017
DOI: 10.1128/jcm.00358-17
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Sequencing of Mycobacterium tuberculosis: Are We There Yet?

Abstract: Whole-genome sequencing has taken a leading role in epidemiologic studies of tuberculosis, but thus far, its real-time clinical utility has been low, in part because of the requirement for culture. In their report in this issue, Votintseva et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Much progress has been made in the field of WGS-based TB diagnostics, including improved procedures for the extraction and enrichment of mycobacterial nucleic acids from sputum samples for downstream WGS (60,61) and the development of automated bioinformatics pipelines, such as CASTB, KvarQ, Mykrobe Predictor TB, PhyResSE, and TBProfiler, for species identification, lineage classification, and detection of resistance-associated mutations for first-and second-line drugs (reviewed in reference 62). The implementation of WGS/next-generation sequencing (NGS)-based diagnostic technologies is certainly not free from technical and economic challenges (63,64), but the time-saving advantages to this method are clinically important, costs continue to decline (61,(64)(65)(66)(67), and targeted NGS has been demonstrated to be a reliable alternative to WGS when culture is not feasible (68).…”
Section: Discussionmentioning
confidence: 99%
“…Much progress has been made in the field of WGS-based TB diagnostics, including improved procedures for the extraction and enrichment of mycobacterial nucleic acids from sputum samples for downstream WGS (60,61) and the development of automated bioinformatics pipelines, such as CASTB, KvarQ, Mykrobe Predictor TB, PhyResSE, and TBProfiler, for species identification, lineage classification, and detection of resistance-associated mutations for first-and second-line drugs (reviewed in reference 62). The implementation of WGS/next-generation sequencing (NGS)-based diagnostic technologies is certainly not free from technical and economic challenges (63,64), but the time-saving advantages to this method are clinically important, costs continue to decline (61,(64)(65)(66)(67), and targeted NGS has been demonstrated to be a reliable alternative to WGS when culture is not feasible (68).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of DST was obtained from 62% of cases, with complete concordance with phenotypic drug susceptibility reference testing. Costs and turn‐around time ranged from 96 to 198 £, and from 44 to 16 h, respectively, however the variability in the quality of results deserves attention …”
Section: Molecular Dstmentioning
confidence: 99%
“…Costs and turnaround time ranged from 96 to 198 £, and from 44 to 16 h, respectively, however the variability in the quality of results deserves attention. 165,166 A different approach for performing DST prediction directly from specimens is the use of a targeted NGS. The Next Gen-RDST assay was developed with the intent to provide molecular DST for seven drugs, and a pilot study on 176 sputum specimens showed an accuracy of 97% compared with pDST.…”
Section: Sequencingmentioning
confidence: 99%
“…18,19 Previous studies have illustrated the potential for a less than 24-hour turnaround time from DNA extraction to clinically relevant results with MinION for generating antibiotic tuberculosis susceptibility profiles. 20,21 The MinION nanopore sequencer has been used successfully for rapid identification of pathogens from positive blood culture bottles, 19 but this investigation by Grumaz and colleagues 7 is the first description of the use of MinION for detecting pathogens directly from blood samples from septic patients. In this study, four septic patients were evaluated using two blood samples from each septic patient.…”
mentioning
confidence: 99%